AN ANALYSIS OF JAVANESE SLANG USED BY STREET VENDORS IN MALIOBORO - MANGGARRANI, MARIA DITA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Yogyakarta is one of the places where Javanese language is developed.The language is used from generations to generations. People say that Yogyakarta is the real Java city. However, the slang of Javanese is also developed in this place. It is known as Boso Walikan Yogya or Boso Prokem. This Javanese slang is a kind of modifications of ngoko Javanese which is reversed in the Javanese writing order. In this study, the researcher identified; (1) What the Javanese slang words used by street vendors in Malioboro are; (2) What the characteristics of Javanese slang used by street vendors in Malioboro are; (3) How the social context of Javanese slang is reflected in street vendors’ daily conversation.The respondents were 26 street vendors in Malioboro aged 30-60 yearsold. The researcher proposed qualitative approach to describe the phenomena of Javanese slang and the answer of the research problems. The type of the study was case study because the researcher needed to do deep investigation about the usage of Javanese slang in street vendors’ daily conversations.There were 105 Javanese slang words used by the street vendors inMalioboro. The researcher gave additional explanation about the meaning of each word to make the data are clearer. The Javanese slang words found are varied and can be used freely, unfortunately, some of them are rude and vulgar therefore the speaker needs to know about the hearer and situation around them as well. Characteristics of the words are creative, flippant, fresh, and short lived. The Javanese slang is used to conceal some topics, such as money, the street vendors’ children, food and beverage, and also people and condition around. In this study, the researcher focused on the slang words, the characteristics of slang, and how the social context of Javanese slang is reflected in street vendors’ interaction. The researcher suggests the next researcher who wants to conduct similarresearch to understand the theory of sociolinguistics, especially the theory related to slang. Furthermore, the next researcher can investigate another aspect of slang, such as the reason of slang usage, and the comparison between slang differences to be the next case study.